Cannabis and Endocannabinoid System - Somchai Amornyotin (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2021)
The endocannabinoid system is involved in various physiological pathways in the human body. A large number of endogenous cannabinoids have been acknowledged, and cannabinoid receptor type 1 (CB-1) and cannabinoid receptor type 2 (CB-2) have been categorized. The activation of endocannabinoid system could regulate the activity in several neural pathways. The complex functions of this system have generated multiple new targets for pharmacotherapies. Several research studies have concentrated on these issues. However, these efforts have been generally unsuccessful. Although cannabinoids have therapeutic potential, their psychoactive properties have largely limited their usage in clinical practice. In this review, the author brieﬂy summarized the knowledge of cannabis and the endocannabinoid system.